1999
DOI: 10.1073/pnas.96.7.3584
|View full text |Cite
|
Sign up to set email alerts
|

Engineering precision RNA molecular switches

Abstract: Ligand-specific molecular switches composed of RNA were created by coupling preexisting catalytic and receptor domains via structural bridges. Binding of ligand to the receptor triggers a conformational change within the bridge, and this structural reorganization dictates the activity of the adjoining ribozyme. The modular nature of these tripartite constructs makes possible the rapid construction of precision RNA molecular switches that trigger only in the presence of their corresponding ligand. By using simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
237
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(247 citation statements)
references
References 40 publications
4
237
0
5
Order By: Relevance
“…Clearly, the fact that the constitutively active ribozyme caused potent inhibition of virus replication in all cases indicates that the aptazyme approach should be universally functional with optimized aptazymes. Artificial aptazymes have been mostly developed in vitro and in bacteria, where aptazymes with high induction rates were generated by high-throughput selection (12,13,20,33). However, only a few aptazymes have been reported to be functional in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, the fact that the constitutively active ribozyme caused potent inhibition of virus replication in all cases indicates that the aptazyme approach should be universally functional with optimized aptazymes. Artificial aptazymes have been mostly developed in vitro and in bacteria, where aptazymes with high induction rates were generated by high-throughput selection (12,13,20,33). However, only a few aptazymes have been reported to be functional in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aptazymes have been extensively developed and studied in vitro, in bacteria, and in yeast (6,12,13,(19)(20)(21)(22). Their application in mammalian systems, however, has been challenging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical study shows that RNAs exhibiting very different secondary structures with near-groundstate energy, i.e., potential riboswitches, are relatively frequent and easily accessible in 7SL/SRP 300-400 signal recognition particle ubiquitous [124] vault 80-100 part of vault particle vertebrata Y 80-100 part of Ro particle metazoa tmRNA 300-400 tags protein for proteolysis bacteria, chloroplasts, cyanoplasts [457] miRNA ∼22 post-transcriptional regulation multicellular organisms [131] gRNA 40-80 RNA editing kinetoplastids [156] evolution [108]. Artificial riboswitches have been explored for biotechnological applications [378,207,364] and it has been demonstrated that such constructs can be specifically triggered by means of small "modifier" RNAs [277,142].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic RNA thermometers based on ribozyme activity 17 such aptazymes have been applied in vivo for gene-regulatory purposes only after the discovery of catalytically well-behaved, fast-cleaving variants of the hammerhead ribozyme comprising stem I/II interactions. [18][19][20] In our opinion, ribozyme-based devices have the advantage of almost universal applicability for controlling RNA functions.…”
Section: Thermozymesmentioning
confidence: 99%